Prevalence of foot problems in people with inflammatory arthritis in Singapore. Issue 1 (December 2016) - Carter, K.; Lahiri, M.; Cheung, P.; Santosa, A.; Rome, K.
Abstract Background Foot problems are highly prevalent in people with inflammatory arthritis reported from studies in the UK, Europe and New Zealand, but there is limited evidence from Southeast Asia. The study aim was to evaluate the prevalence of foot problems in people with inflammatory arthritis in Singapore. Methods People with inflammatory arthritis were recruited from the rheumatology outpatient clinic of a tertiary hospital in Singapore. Disease and clinical characteristics included age, sex, disease duration, current blood tests and medications. The Leeds Foot Impact Scale was used to evaluate foot impairment/disability and the Modified Health Assessment Questionnaire was used to assess global function. Results We recruited 101 people with inflammatory arthritis, of which 50 % were female. The majority of participants were Chinese (70 %). The mean (SD) age was 52 (15) years, and the mean (SD) disease duration was 9.3 (0.3) years. The most commonly reported inflammatory arthritic conditions were rheumatoid arthritis (46), gout (31) and spondyloarthritis (15 %). The mean (SD) of the total Leeds Foot Impact Scale was 17 (13) indicating moderate to severe levels of foot impairment and activity limitation. Over 80 of participants reported foot pain during the course of their condition, and 48 % reported current foot pain. Despite the high prevalence of foot pain, only 21 participants (21 %) had been referred to a podiatrist. Conclusion This is the first study to investigate the prevalence of foot problems in people with inflammatory arthritis from Singapore. The majority of the participants reported foot problems, but had not been referred to a podiatry service.